Collaborative Overview of coronaVIrus impact on ORTHopaedic training in the UK (COVI - ORTH UK). Issue 6 (December 2021) - Jayatilaka, Malwattage Lara Tania; As-Sultany, Mohammed; Gabr, Ayman; Thornton, Luke; Graham, Simon; Mason, Lyndon; Farrar, Nicholas Greville; ,; Abdalla, Samir; A'Court, Jamie; Allport, Jack; Andrew, Stefanie; et al.
Abstract: Introduction: COVID-19 was declared a pandemic by the World Health Organization on the 11th of March 2020 with the NHS deferring all non-urgent activity from the 15th of April 2020. The aim of our study was to assess the impact of COVID-19 on Trauma and Orthopaedic trainees nationally. Methods: Trauma and Orthopaedic (T&O) specialty trainees nationally were asked to complete an electronic survey specifically on the impact of COVID-19 on their training. This UK based survey was conducted between May 2020 and July 2020. Results: A total of 185 out of 975 (19%) T&O specialty trainees completed the survey. Redeployment was experienced by 25% of trainees. 84% of respondents had experienced a fall in total operating numbers in comparison with the same time period in 2019. 89% experienced a fall in elective operating and 63% experienced a fall in trauma operating. The pandemic has also had an effect on the delivery of teaching, with face to face teaching being replaced by webinar-based teaching. 63% of training programmes delivered regular weekly teaching, whilst 19% provided infrequent sessions and 11% provided no teaching. Conclusion: This study has objectively demonstrated the significant impact of the COVID-19 pandemic on all aspects of T&O training. Highlights: COVID – 19 has had an impact on trauma and orthopaedic training. COVID – 19 has affected trauma and orthopaedic training across the United Kingdom. COVID – 19 has effected the delivery of regional teaching in trauma and orthopaedics.